TEACHING PHYSICAL SCIENCE: SHOULD WE IMPLEMENT TEACHER-CENTERED CAI OR STUDENT-CENTERED CAI AT SECONDARY SCHOOL LEVEL IN INDIA? - Siddiqui, Uzma; Khatoon, Tahira (European Scientific Journal, ESJ, 2013)
This study investigated the effects of traditional instruction, teacher-centered computer assisted instruction (CAI) and student-centered computer assisted instruction on secondary school students’ achievement in Physical Science. A total of 120 tenth-grade secondary school students participated in this randomized pretest-posttest control group experimental study. These students were randomly divided into three groups, namely, control group (n = 40), Teacher-centered CAI experimental group (n = 40) and Student-centered CAI experimental group (n = 40). During a period of 5 weeks, control group was taught by traditional instruction, whereas Teacher-centered CAI and Student-centered CAI experimental groups were subjected to teacher-centered CAI and student-centered CAI methods respectively. An analysis of covariance on the Physical Science Achievement Test posttest scores with students’ pretest scores as the covariate showed that the teacher-centered CAI approach was more effective in enhancing the students’ achievement in Physical Science than traditional instruction and student-centered CAI method. It is, therefore, suggested teacher-centered CAI method is a good alternative for teaching Physical Science at secondary school level in India.